A rite of passage: a mixed methodology study about knowledge, perceptions and practices of menstrual hygiene management in rural Gambia - Vishna Shah; Helen M. Nabwera; Fatou Sosseh; Yamundao Jallow; Ebrima Comma; Omar Keita; Belen Torondel (BMC, 2019)
Abstract Background Appropriate menstrual hygiene management (MHM) is impeded by taboos and secrecy surrounding menstruation. Unhygienic menstrual practices and unpreparedness for managing menstruation has been associated with adverse health and social outcomes among adolescent girls. In The Gambia, there is limited data on menstrual practices among girls and women in rural communities and the sources of information about menstruation for the adolescents. This study aimed to explore knowledge, preparedness and practices of menstruation and its management among adolescents, mothers and teachers in rural Gambia. Methods A mixed methods study was conducted in the rural Kiang West district of The Gambia. Twenty focus group discussions and thirteen in-depth interviews were conducted among mothers, adolescents and teachers to explore their views on menstruation, cultural beliefs, sources and level of knowledge on menstruation and MHM practices. In addition, a survey was done among 331 school girls to assess their knowledge, practices and attitudes of menstruation and its management. Inductive content analysis was used to analyse the qualitative data, and descriptive analysis and chi-squared tests were used to analyse quantitative data. Results All participants had different levels of knowledge about menstruation. Knowledge score was higher among post-menarche girls compare with pre-menarche girls (p = 0.0001). All groups expressed difficulties, embarrassment and shame in relation to discussing menstruation. Two thirds of the surveyed girls reported having learnt about menstruation before menarche, however at menarche most felt unprepared. Teachers were the main source of information, but when asking for advice most girls preferred to ask their mothers. Mothers reported facing difficulties in discussing menstruation with their children and felt that boys did not need to be taught about it, however boys were very curious to know about. Most girls used reusable cloth unless they are given free pads from school. Conclusion Taboos, secrecy and embarrassment associated with discussing menstruation hinder adolescents from seeking advice from parents and teachers on appropriate MHM practices. Strategies to encourage positive social norms towards menstruation would help to promote more open discussions about it at the family, community and national level, which will support improvements in MHM in this and similar communities in low and middle income settings.